Teaching English through Modern Internet Resources - Ermamatova Qunduzoy Sherali qizi, (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
Modern Internet resources play an important role in making the English language teaching process more effective and interactive. This article presents the best online lesson plans, games, and communication tools for English teachers. Resources such as Minecraft Adventures in English, Kahoot, Breaking News English and Film English are used to engage students and develop their language skills. The article gives tips to teachers on how to make their lessons more interesting and effective.